Legal Uncertainty in the Application of Simple Proof in Bankruptcy Cases and Suspension of Debt Payment Obligations - Prasetyo, Rahmad; Barthos, Megawati (Pelopor Publikasi Akademika, 2024)
The Asian monetary crisis of 1997 triggered significant changes in the Indonesian legal system, including the reform of bankruptcy laws marked by the emergence of Law No. 4 of 1998 and later Law No. 37 of 2004 regarding Bankruptcy and Suspension of Debt Payment Obligations (PKPU). This crisis underscored the need for a fair and effective debt resolution mechanism. This research uses a normative juridical approach with descriptive analysis methods to examine the application of the pari passu pro rata partem concept and simple proof in the Bankruptcy Law. The data sources used are secondary data consisting of legislation, legal literature, and related court decisions. The results show that the practice of applying simple proof often leads to inconsistency in judges' decisions because the law does not clearly specify the definition of